In vitro Antiradical, Antimicrobial and Antiproliferative Activities and Phytochemical Compositions of Endemic Alcea calvertii (Boiss) Boiss. Flowers - Keser, Serhat; Keser, Fatma; Tekin, Suat; Kaygılı, Omer; Turkoglu, İsmail; Demir, Ersin; Turkoglu, Semra (My University, 2020)
Alcea calvertii (Boiss) Boiss. is belonged to Malvaceae family, and it is a perennial herbaceous endemic plant.Alcea genus plants are grown as ornamental plants in the gardens. In the present study, the antiproliferative,antimicrobial, antiradical activities and phytochemical compositions of ethanol, water, methanol and acet oneextracts of A. calvertii flowers were examined. A. calvertii flowers water, ethanol, methanol and acetone extractsare lower scavenged DPPH, ABTS and OH radicals than standard antioxidant trolox. A. calvertii flowers containvitamins, sterols, flavonoids and phenolic acids, dominated by vanillic acid, gallic acid, catechin, ?-tocopherol,ergosterol and vitamin D. A. calvertii flowers water extract showed better antiproliferative activities than otherextracts against to MCF-7 and HCT-116 cell lines. A. calvertii flowers methanol extract showed higherantiproliferative effect against to LNCaP cell lines.
Keywords: Biyoloji; Patoloji; Mikrobiyoloji; Parazitoloji; Kimya; Tıbbi; Onkoloji; Viroloji; Biyokimya ve Moleküler Biyoloji